Information processing in an optoelectronic display system - Bushma, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Generalized analytical description of a display system based on the functional approach to data processing in the human-machine environment has been made. Logic properties of a separate display element have been investigated. It has been shown that polar elements realize the logical function of negation of implication and non-polar ones process the data according to the inequality function. Equivalent circuits in the Boolean basis that can replace polar and non-polar information area elements in logical functional modeling of display units have been presented.